Pengaruh Profitabilitas, Kepemilikan Manajerial, Ukuran Perusahaan dan Leverage terhadap Nilai Perusahaan: Studi Empiris pada Perusahaan Manufaktur Sub Sektor Food and Beverage yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Ambar Dwi Narwatih; Slamet Mudjijah (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
This research aims to determine the effect of Profitability, Managerial Ownership, Company Size and Leverage on Company Value in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the 2019–2023 period. The sample for this research is 24 companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the 2019-2023 period. This research was carried out using the multiple linear regression method assisted by the SPSS version 22.0 program and Microsoft Excel 2010. The results of the research show that Profitability has an effect on Company Value, Managerial Ownership has no effect on Company Value, Company Size has a negative effect on Company Value, Leverage has an effect on Company Value.